إسهامات محمد بن كيسان النحوي المتوفى سنة (299هـ) في الأصول النحوية : دراسة تحليلية - قحطاني، علي محمد علي (Kulliyah of Islamic Revealed Knowledge and Human Sciences,al-Jami'at al-Islamiyyah al- 'Alamiyyah Maliziya, 2019)
This study explores the grammatical foundations of the prominent linguist who appeared in a very important era of asceticism and language, namely the great scholar Muhammad ibn Kaisan al-Nahawi who died in 299 AH. The study adopts the inductive method to collect the scientific material related to the evidence of the grammatical origins of ibn Kaisan which formed his grammatical and morphological views. It then analyses the scientific material and devises the grammatical determined by ibn Kaisan in his writings. Among the prominent results of the study is that ibn Kaisan is the first to have written on the fundamentals of grammar and the first grammatical scholar interested in the fundamentals of grammar as a science independent of grammar. His works are a fertile area for the study of Arabic grammar. He depended heavily on listening to various sources, the most important of which is the Quran and its various readings. He quotes the Holy Quran and its verses as evidence for grammar. Ibn Kaisan regarded analogy as the second source of grammar. He derived several grammatical rulings overlooked by his predecessors such as al-Qubh (ugliness) and al-Karahah (hatred). Furthermore, in line with the standard approach of Arab linguists, ibn Kaisan did not refer to the Prophet's Hadith in his grammatical reasoning. Ibn Kaisan paved the way for subsequent scholars to establish the fundamentals of grammar as a result of the advancement and maturity of this field of inquiry. This paper concludes that ibn Kaisan classified the foundations of grammar as listening, consensus, and accompanying the origin. This classification was followed by the majority of subsequent scholars even if it is not always explicit, although some did acknowledge ibn Kaisan's influence.